2020
DOI: 10.2967/jnumed.119.232017
|View full text |Cite
|
Sign up to set email alerts
|

Management of Patients with Renal Failure Undergoing Dialysis During131I Therapy for Thyroid Cancer

Abstract: Compliance with ethical standards-Conflict of interest: None.-Research involving human participants: All procedures performed in studies involving human participants were in accordance with the ethical standards of the institutional and/or national research committee and with the 1964 Declaration of Helsinki and its later amendments or comparable ethical standards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…After a full-text screening we excluded another 31 studies for various reasons: they gave no relevant information on dosing or aspects related to dosing ( n = 18), they addressed only the radiation safety of staff ( n = 5), described renal imaging ( n = 5), or were review ( n = 3). A total of 34 studies remained for inclusion in this systematic review (Akers et al 2016 ; Aktaş et al 2008 ; Alevizaki et al 2006 ; Bhat et al 2017 ; Courbon et al 1997 , 2006 ; Culpepper et al 1992 ; Daumerie et al 1996 ; Demko et al 1998 ; Driedger et al 2006 ; El-Zeftawy et al 2017 ; Fofi et al 2013 ; Holst et al 2005 ; Howard and Glasser 1981 ; Jiménez et al 2001 ; Kaptein et al 2000 ; Kode et al 2017 ; Laffon et al 2008 ; Magné et al 2002 ; McKay and Malaroda 2019 ; McKillop et al 1985 ; Mello et al 1994 ; Minamimoto et al 2007 ; Miyasaka et al 1997 ; Morrish et al 1990 ; Pahlka and Sonnad 2006 ; Sinsakul and Ali 2004 ; Tobes et al 1989 ; Toriihara et al 2015 ; Toubert et al 2001 ; Vermandel et al 2020 ; Wang et al 2003 ; Willegaignon et al 2010 ; Yeyin et al 2016 ). The selection process is illustrated in a PRISMA flow diagram (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After a full-text screening we excluded another 31 studies for various reasons: they gave no relevant information on dosing or aspects related to dosing ( n = 18), they addressed only the radiation safety of staff ( n = 5), described renal imaging ( n = 5), or were review ( n = 3). A total of 34 studies remained for inclusion in this systematic review (Akers et al 2016 ; Aktaş et al 2008 ; Alevizaki et al 2006 ; Bhat et al 2017 ; Courbon et al 1997 , 2006 ; Culpepper et al 1992 ; Daumerie et al 1996 ; Demko et al 1998 ; Driedger et al 2006 ; El-Zeftawy et al 2017 ; Fofi et al 2013 ; Holst et al 2005 ; Howard and Glasser 1981 ; Jiménez et al 2001 ; Kaptein et al 2000 ; Kode et al 2017 ; Laffon et al 2008 ; Magné et al 2002 ; McKay and Malaroda 2019 ; McKillop et al 1985 ; Mello et al 1994 ; Minamimoto et al 2007 ; Miyasaka et al 1997 ; Morrish et al 1990 ; Pahlka and Sonnad 2006 ; Sinsakul and Ali 2004 ; Tobes et al 1989 ; Toriihara et al 2015 ; Toubert et al 2001 ; Vermandel et al 2020 ; Wang et al 2003 ; Willegaignon et al 2010 ; Yeyin et al 2016 ). The selection process is illustrated in a PRISMA flow diagram (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Another study recommended a 30% reduction in dose for ablative or adjuvant therapies and a dose based on pretherapeutic dosimetry studies for metastatic patients. This study based these recommendations on absorbed dose in the bone marrow estimated from normalised measured whole-body activity (Vermandel et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Vogel K et al [26] stipulated that the biological half-life of 131 I was signi cantly in uenced by eGFR; a decrease in GFR may signi cantly prolong the half-life of 131 I. Similarly, in some studies, the prescribed activity of 131 I in patients with renal insu ciency is reduced by approximately 30% or 50% to compensate for the prolonged clearance of radioiodine [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Alevizaki et al used a 40%-50% activity reduction of 131 I and found that none of their patients experienced short-term side effects or had detectable thyroglobulin levels on their first posttherapy evaluation (n 5 5; the inclusion criterion was end-stage renal disease) (24). Vermandel et al concluded that an approximately 30% reduction from the nominal 131 I dose struck the best balance between hematologic toxicity and treatment efficacy (n 5 6; the inclusion criterion was end-stage renal disease undergoing hemodialysis) (25). Following their lead, we chose to reduce the dose despite the fact that some of the literature recommended no change in, or even increased, doses; our case involved a 40% reduction from our typical 1,850 MBq (50 mCi) to 1,110 MBq (30 mCi) to minimize radiation exposure of marrow secondary to reduced clearance of 131 I.…”
Section: Casementioning
confidence: 99%
“…Radi oactive iodine (RAI) is considered a key treatment modality for hyperthyroidism and differentiated metastatic thyroid cancer; its use for these conditions was first documented in 1946 (1). 131 I is used to treat Graves disease (therapeutic dose, 370-555 MBq [10][11][12][13][14][15]), toxic multinodular goiter (therapeutic dose, 555-1,110 MBq [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]), and thyroid cancer (therapeutic dose, 1,110 MBq [30 mCi] or more) (2)(3)(4).…”
mentioning
confidence: 99%